2016
DOI: 10.1186/s40168-016-0193-y
|View full text |Cite
|
Sign up to set email alerts
|

Mungo bean sprout microbiome and changes associated with culture based enrichment protocols used in detection of Gram-negative foodborne pathogens

Abstract: BackgroundFresh sprouted seeds have been associated with a number of large outbreaks caused by Salmonella and Shiga toxin-producing E. coli. However, the high number of commensal bacteria found on sprouted seeds hampers the detection of these pathogens. Knowledge about the composition of the sprout microbiome is limited. In this study, the microbiome of mungo bean sprouts and the impact of buffered peptone water (BPW) and Enterobacteriaceae enrichment broth (EE-broth)-based enrichment protocols on this microbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
3
5
0
Order By: Relevance
“…In both samples, the dominant phylum of uncultured samples (before cultivation, 0 h) was Proteobacteria (sample A 91.9% and sample B 97%), followed by Firmicutes (sample A 7.9% and sample B 2.6%), while Bacteroidetes were more or less frequent (in both samples under 0.5%). This corresponds partly to the findings of Margot et al [ 26 ], who analyzed the uncultured bacteriome of mungo bean sprouts by 16S rRNA sequencing. Margot et al also found Proteobacteria as the most prevalent phylum (90.4%), but Firmicutes (0.6%) were exceeded by Bacteroidetes (8.8%) [ 26 ].…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…In both samples, the dominant phylum of uncultured samples (before cultivation, 0 h) was Proteobacteria (sample A 91.9% and sample B 97%), followed by Firmicutes (sample A 7.9% and sample B 2.6%), while Bacteroidetes were more or less frequent (in both samples under 0.5%). This corresponds partly to the findings of Margot et al [ 26 ], who analyzed the uncultured bacteriome of mungo bean sprouts by 16S rRNA sequencing. Margot et al also found Proteobacteria as the most prevalent phylum (90.4%), but Firmicutes (0.6%) were exceeded by Bacteroidetes (8.8%) [ 26 ].…”
Section: Resultssupporting
confidence: 88%
“…They are known from previous analyses (data not shown) to contain quite high loads of microorganisms and also due their high potential for microbial contamination (a difficult journey from farm to consumer). As they are high in raw consumption (preservation of all nutrients), they can serve as an excellent foyer for ARB into the human gastrointestinal microbiome, and their consumption can lead to food poisoning [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, a conserved segment of a hypervariable region of the 16S rDNA gene is used. In recent years, the field of metagenomics has flourished and published studies now include insights into the microbiomes of cilantro [ 1 ], spinach [ 2 ], bean sprouts [ 3 ], kimchi [ 4 ], kefir [ 5 ], meat [ 6 ], wine [ 7 ], and cheese [ 8 – 13 ]. The composition of the native microbiota in these food products may help determine property characteristics contributed to by microorganisms such as flavor, texture, color, aroma, shelf-life, and spoilage.…”
Section: Introductionmentioning
confidence: 99%
“…The results show the dominance of Proteobacteria, Actinobacteria, Firmicutes, and Bacteroidetes phyla on broccoli florets, as seen on other fresh vegetables (10,11,30). Such bacterial diversity of the broccoli phyllosphere is greater than that predicted by culture-based analysis, which detects only a few bacterial species (31), and suggests that the majority of phyllosphere bacteria on broccoli florets are novel.…”
Section: Discussionmentioning
confidence: 78%